Automatic Bottle Filling System Using PLC/SCADA - Deya Thakar; Priyanshi Prajapati; Prof. Dr. Kaushika Patel (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This project presents an Automatic Bottle Filling System using Siemens S7-1200 PLC and SCADA for real-time monitoring. It uses an IR sensor to detect bottles, an ultrasonic sensor to check liquid levels, and a mini pump to fill the bottles. The conveyor is controlled using DC motors and relays, with logic programmed via TIA Portal V16. The system improves accuracy, reduces manual effort, and is suitable for small to medium-scale industries like beverages and dairy. It provides an efficient, automated solution for modern production lines.
Keywords: Automation; PLC; SCADA; Bottle Filling System; Siemens S7-1200; TIA Portal; IR Sensor; Ultrasonic Sensor; Conveyor Mechanism; Industrial Control; Mini Water Pump